Kadına Karşı Ayrımcılığın Önlenmesi Sözleşmesinin (CEDAW) Müslüman Ülke Kanunlarına Etkileri / The Impact of the Convention on the Elimination of all Forms of Discrimination against Women (CEDAW) on Muslim Countries Laws - Yalçın, İsmail (Journal of History Culture and Art Research, 2017)
Abstract The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), which was adopted by the UN and by most countries of the world, has influenced women’s rights and led to important developments in countries party to the treaty. Most Islamic countries have put reservations on some articles of the Convention citing Islamic law practices and local culture while ratifying the Treaty, but then have removed some of these reservations by passing adaptive laws. While some of these regulations such as women’s share in inheritance, their testimony, and obedience to husband have a strong connection to main religious sources, others such as reduced sentences in honor killings, women carrying their own surname, voting in elections, and female genital mutilation are based on customary and tacit law judgments. Through CEDAW, Muslim countries have faced pressure and criticism in international platforms with the allegation that their laws on person, family, inheritance, punishments, citizenship, and procedural law involve discrimination against women. With the influence of the international atmosphere, women’s movements have risen in Muslim countries and through legal changes there has been developments with regard to women’s rights in line with CEDAW. Even though after CEDAW there is some convergence between the Islamic World and the West in terms of women’s rights and gender equality, differences based on culture continue to exist. Öz Dünya ülkelerinin büyük çoğunluğunun taraf olduğu Birleşmiş Milletler Kadına Karşı Her Türlü Ayrımcılığın Önlenmesi Sözleşmesi (CEDAW), imzalandığı günden bu tarafa kadın hakları alanında önemli gelişmelere sebep olmuş ve taraf ülkeleri etkilemiştir. İslam ülkelerinin birçoğu, İslam hukuku uygulamalarından veya yerel kültürden kaynaklanan farlılıklar sebebiyle, katılmadığı maddelere çekince koyarak Sözleşmeyi onaylamış ancak sonradan bu çekincelerin bir kısmı yasal düzenlemelerde değişiklik yapılarak kaldırılmıştır. Bu düzenlemelerden kadının miras payı, şahitliği, kocasına itaati gibi bazılarının dinin ana kaynaklarıyla kuvvetli irtibatı söz konusu iken, namus cinayetlerinde ceza indirimi, kadının kendi soyadını taşıması, seçimlerde oy kullanması, kadın sünneti gibi bir kısmında örfi içtihatlar ağır basmaktadır. CEDAW vesilesiyle Müslüman ülkeler, şahıs, aile, miras, ceza, vatandaşlık, usul hukuku, gibi kanunlarında kadına karşı ayrımcılık içeren maddeler bulunduğu iddiasıyla uluslararası platformlarda baskı ve eleştiri ile karşılaşmıştır. Uluslararası atmosferin etkisiyle Müslüman ülkelerde kadın hareketleri yükselmiş ve yasal değişiklerle beraber kadın hakları alanında CEDAW doğrultusunda gelişmeler görülmüştür. CEDAW sonrası İslam Dünyası ve Batı arasında kadın hakları ve kadın erkek eşitliği konusuna bakışta kısmî bir yakınlaşma olmakla birlikte kültür farkına dayalı farklılıklar devam etmektedir.